The Racial Glass Ceiling : Subordination in American Law and Culture - Brooks, Roy L. (New Haven, CT : Yale University Press, 2018)
A compelling study of a subtle and insidious form of racial inequality in American law and culture. Why does racial equality continue to elude African Americans even after the election of a black president? Liberals blame white racism while conservatives blame black behavior. Both define the race problem in socioeconomic terms, mainly citing jobs, education, and policing. Roy Brooks, a distinguished legal scholar, argues that the reality is more complex. He defines the race problem African Americans face today as a three-headed hydra involving socioeconomic, judicial, and cultural conditions. Focusing on law and culture, Brooks defines the problem largely as racial subordination the act of impeding racial progress in pursuit of nonracist interests. Racial subordination is little understood and underacknowledged, yet it produces devastating and even deadly racial consequences that affect both poor and socioeconomically successful African Americans. Brooks addresses a serious problem, in many ways more dangerous than overt racism, and offers a well-reasoned solution that draws upon the strongest virtues America has exhibited to the world.
Frontmatter -- Contents -- Preface -- Acknowledgments -- Introduction: A New Understanding of Racial Subordination -- One. The Spirit of Brown -- Two. Juridical Subordination -- Three. Race and Culture -- Four. Cultural Subordination Through Cultural Diversity -- Epilogue: Unrelenting Racial Progress -- Appendix A: Diagram of Main Arguments -- t
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 20. Sep 2019)
Keywords: African Americans -- Economic conditions -- 21st century; African Americans -- Social conditions -- 21st century; Racism -- United States -- History -- 21st century; SOCIAL SCIENCE / Discrimination & Race Relations